Utilization of Instagram Social Media in Increasing Product Sales, RR Management Case Study - Ningsih, Wiwin Fitria; Aggasi, Abbyzar (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This research was conducted at a business called RR Management which focuses on accessories, how promotional strategies through the use of Instagram social media can increase product sales at RR Management, Sumbawa to find out what promotional strategies are used to increase product sales through the use of Instagram social media at RR Management located on Jln Melati. No. 06, Kel. Bugis, Sumbawa Besar. The method in this research is to use a qualitative method with a descriptive approach to obtain the data desired by the researcher, namely that RR Management has utilized the features in Instagram as a promotional medium, the use of Instagram media in sales has increased the number of product sales and can attract many consumers. . Instagram has an important role for RR Management, through Instagram RR Management can exchange information through content such as photos and videos. The posts uploaded to RR Management's Instagram are the emergence of disseminating information to consumers. The @cv.rrmanagement account to attract a lot of attention from the public, RR Management should collaborate with influencers on Instagram. Make more use of the Live Instagram feature when new items come in so that information is spread to a wider audience. RR Management needs to be improved more consistently in uploading content on Instagram so that the @cvrrmanagement account can attract lots of customers on Instagram.